Inter-subunit interactions drive divergent dynamics in mammalian and Plasmodium actin filaments - Douglas, Ross G.; Nandekar, Prajwal; Aktories, Julia-Elisabeth; Kumar, Hirdesh; Bitsch, Rebekka; Sattler, Julia M.; Singer, Mirko; Lepper, Simone; Sadiq, Kashif; Wade, Rebecca C.; Frischknecht, Friedrich (PLoS biology, 2018)
Cell motility is essential for protozoan and metazoan organisms and typically relies on the dynamic turnover of actin filaments. In metazoans, monomeric actin polymerises into usually long and stable filaments, while some protozoans form only short and highly dynamic actin filaments. These different dynamics are partly due to the different sets of actin regulatory proteins and partly due to the sequence of actin itself. Here we probe the interactions of actin subunits within divergent actin filaments using a comparative dynamic molecular model and explore their functions using Plasmodium, the protozoan causing malaria, and mouse melanoma derived B16-F1 cells as model systems. Parasite actin tagged to a fluorescent protein (FP) did not incorporate into mammalian actin filaments, and rabbit actin-FP did not incorporate into parasite actin filaments. However, exchanging the most divergent region of actin subdomain 3 allowed such reciprocal incorporation. The exchange of a single amino acid residue in subdomain 2 (N41H) of Plasmodium actin markedly improved incorporation into mammalian filaments. In the parasite, modification of most subunit-subunit interaction sites was lethal, whereas changes in actin subdomains 1 and 4 reduced efficient parasite motility and hence mosquito organ penetration. The strong penetration defects could be rescued by overexpression of the actin filament regulator coronin. Through these comparative approaches we identified an essential and common contributor, subdomain 3, which drives the differential dynamic behaviour of two highly divergent eukaryotic actins in motile cells.
Gesehen am 30.07.2018